Adsorption of Lead Ions from Aqueous Solution onto Activated Carbon and Chemically-Modified Activated Carbon Prepared from Date Pits - Mohamed Abdulkarim; Fahmi Abu Al-Rub (Adsorption Science & Technology)
Date pits, i.e. agricultural wastes, were converted into activated carbon by air and phosphoric acid activation. The surfaces of some of the prepared activated carbons were modified chemically using 8-hydroxyquinoline. The carbons prepared by both air and phosphoric acid activation showed surface areas of 864.8 m 2 /g and 502.2 m 2 /g, respectively, and micropore volumes of 0.298 cm 3 /g and 0.126 cm 3 /g, respectively. The adsorption of Methylene Blue onto the prepared activated carbon demonstrated its very high adsorption capacity. The adsorption of lead ions on both carbons, i.e. activated and chemically-modified, was studied under different conditions. The experimental results showed that both types of carbon gave a relatively large maximum lead ion uptake, the increase in the uptake as a result of chemical modification being insignificant. Lead ion uptake was found to increase by increasing the solution pH — whereby the maximum adsorption of lead ions was obtained at pH 5.2 — and by increasing the initial lead ion concentration. Equilibrium studies showed that the adsorption of lead ions on both adsorbents could be described by the Langmuir and Freundlich isotherm models. Kinetic studies showed that the adsorption of lead ions on the prepared activated carbons followed pseudo-second-order kinetics. The presence of EDTA, acetic acid or citric acid led to a significant decrease of lead ion uptake by the activated carbons.